Profiles of Sugar and Organic Acid of Fruit Juices: A Comparative Study and Implication for Authentication - Jiaxiu Li; Chunling Zhang; Hui Liu; Jiechao Liu; Zhonggao Jiao (Journal of Food Quality)
A comparison of sugar and organic acid profiles among different fruit juices (including apple, pear, peach, grape, sweet cherry, strawberry, and blueberry with various varieties) was performed to assess the possibility for authentication coupled with chemometrics. It was found that the distribution of each sugar and organic acid in juices showed some specific characteristics related to fruit species, despite the fact that great differences in the content existed among different varieties. Sucrose was the most abundant sugar in peach juice, accounting for 58.26–77.11% of the total sugar content. However, in grape, blueberry, and sweet cherry juice, glucose and fructose were the predominant sugars. Pear juice contained the highest level of sorbitol, which contributed to 15.02–43.07% of the total sugar content. Tartaric acid was detected only in grape juice among the seven species of fruit juice, with a proportion of 57.95–89.68% in the total acid content. Malic acid was the predominant organic acid in apple and sweet cherry juice, accounting for 69.92–88.30% and 97.51–98.73% of the total acid content of each species. Citric acid was the predominant organic acid in strawberry and blueberry juice, which contributed to 62.39–83.73% and 73.36–89.56% of the total acid content of each species. With the aid of principal component analysis and linear discriminant analysis (LDA), the juice samples could be successfully classified according to fruit species by using the sugar and/or organic acid composition as analytical data. Combination of sugar and organic acid composition gave the best differentiation of these seven species of juices, with a 100% correct classification rate for both the original and the cross-validation method in LDA. Adding malic/citric into the dataset of the organic acid content may also improve the differentiation effect. Furthermore, the adulteration of sweet cherry juice, blueberry juice, raspberry juice, and grape juice with apple juice, pear juice, or peach juice could also be distinguished from their corresponding pure juices based on sugar and organic acid composition by LDA.